Politician trojan horse issue: The challenge of developing a priority political strategy for facing the 2024 simultaneous elections - Ndona, Yakobus; Siagian, Liber; Ginting, Elisa Br; Faimau, Gabriel (Jurnal Civics: Media Kajian Kewarganegaraan, 2025)
This article examines the concept of "Trojan Horse politics" and the challenges associated with priority-based political development in the context of the 2024 simultaneous elections, using an ethical Trojan Horse strategy from a political philosophy perspective. The research is based on a comprehensive literature review of priority-based political frameworks. Data on moral virtues were gathered from various journal articles, academic papers, government reports, social media, online sources, and expert writings, particularly those of Thomas Aquinas. The data analysis employs philosophical hermeneutics, including verstehen, translation, and interpretation techniques. The study, conducted over three months, reveals that prioritisation is critical in selecting potential political leaders and representatives. Virtue should motivate all competencies, guiding prospective leaders in recognising their calling to address societal issues, crafting a vision, setting political agendas, formulating policy programs, and taking bold actions. Furthermore, it underscores the importance of resilience, the ability to inspire risk-taking, and the stimulation of social capital, charisma, and collective potential in fostering national sustainability and achieving social welfare. In preparation for the 2024 elections, political parties must undertake thorough vetting processes and disclose the histories of their candidates to ensure that elected leaders prioritise the public good.